Aspek Pengembangan Internalisasi Nilai Moderasi Islam pada Santri - Mochamad Chairudin (Proceedings of Annual Conference for Muslim Scholars, 2018)
Pesantren are institutions of educational institutions that still exist from all changes. A manifestation of the development of pesantren that brings the principle of moderation of Islam in Indonesia.Seperti phenomena process of internalization of Islamic Moderation values ​​at Students in boarding Qomaruddin Gresik. Its existence as the oldest cottage on the north coast as the transfer of cultural access but still maintaining the habits of pesantren despite being squeezed by industrialization. This makes the study of the internalization of the Santri Moderation in Qomaruddin Gresik pesantren interesting. This research uses qualitative descriptive approach, case study research, observation data collection method, interview, documentation, and literature review. The concept of internalization of Moderation values ​​in Santri is an attempt to realize the process of taking Islamic Moderation by Santri to be manifested in everyday behavior. The implementation of internalization of Islamic Moderation values ​​in the Islamic School at the Qomaruddin Gresik pesantren is done through the development of efforts in the process of value internalization, the development of strategies and methods and aspects that have an important role in internalizing the value of Islamic Moderation.